A novel strategy to optimize critical information on over the counter labels for older adults. Issue 1 (25th January 2023) - Becker, Mark W.; Kashy, Deborah A.; Harben, Alyssa; Venkatesan, Krishnaa; Rodriguez, Andrew; Kebede, Matt; Martin, Beth; Breslow, Robert; Bix, Laura
Abstract: Background and Aims: Labels designed to communicate critical information are paramount for the safe and effective use of over‐the‐counter medications; in recognition of this, the content and formatting of over the counter (OTC) labels sold in interstate commerce has been regulated for decades. Yet, available studies suggest that consumers frequently rely on limited information during decision making, failing to access the information required in the Drug Facts Label. This is particularly important for older consumers, who are at greater risk for adverse reactions to medicines. In two experiments we objectively evaluate how novel label designs that employ highlighting and a warning label placed on the package's front impact older consumers' attention to, and use of, critical information. Methods: In Experiment 1, 68 OTC patients (65+) engaged with a computer‐based task answering yes/no scenario‐based questions about a drug's appropriateness. In Experiment 2, 63 OTC patients (65+) conducted a forced‐choice task where one of two drugs presented on a computer screen was appropriate for a provided scenario while the other was not. Both tasks required participants to access and use critical label information (i.e., warnings or active ingredients) to respond correctly. Dependent variables analyzed were the proportion of correct responses and time to correct response. Results: Highlighting or placing critical information on the front of the package significantly improved response accuracy and time to correct response in Experiment 1 as compared to responses utilizing the standard label. For Experiment 2, participants were faster and more accurate when critical information was highlighted. Conclusions: Results provide direct measures of the efficacy of novel labeling strategies. This information is relevant for regulations which dictate label design in ways that enhance ease and safety of use of medications for older adults.